2021
DOI: 10.3390/pharmaceutics13091324
|View full text |Cite
|
Sign up to set email alerts
|

Bleomycin Concentration in Patients’ Plasma and Tumors after Electrochemotherapy. A Study from InspECT Group

Abstract: The plasma concentration profile of bleomycin in the distribution phase of patients younger than 65 years is needed to determine the suitable time interval for efficient application of electric pulses during electrochemotherapy. Additionally, bleomycin concentrations in the treated tumors for effective tumor response are not known. In this study, the pharmacokinetic profile of bleomycin in the distribution phase in 12 patients younger than 65 years was determined. In 17 patients, the intratumoral bleomycin con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…Therefore, the results of electroporation associated with chemotherapy combinations vary. In a study of human patients, it was observed that patients diagnosed with cutaneous angiosarcoma had the highest concentrations of BLM (819 mg/g); however, the tumor presented tumor progression and had no response to ECT [ 65 , 66 ], showing a difference in perfusion, vascularization, and response in different tumor types.…”
Section: Treatmentmentioning
confidence: 99%
“…Therefore, the results of electroporation associated with chemotherapy combinations vary. In a study of human patients, it was observed that patients diagnosed with cutaneous angiosarcoma had the highest concentrations of BLM (819 mg/g); however, the tumor presented tumor progression and had no response to ECT [ 65 , 66 ], showing a difference in perfusion, vascularization, and response in different tumor types.…”
Section: Treatmentmentioning
confidence: 99%
“…In this context, it should be considered that the pharmacokinetic pro le of BLM in the distribution phase after bolus injection is not known in each tumor model. Preliminary data from clinical studies in cutaneous cancer concluded that a complete response in ECT-treated lesions can be achieved with a minimal intracellular concentration of 14-18 ng/g [29]. In our study, we used BLM at a dose of 4 U/kg for i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Since the patient was old with several comorbidities and BLM was injected intra-arterially, we additionally reduced the recommended dose by 40% to avoid significant necrosis of the treated area and pulmonary fibrosis. This decision was based on our previous studies on elderly patients treated with ECT in combination with a reduced dose of intravenously administered BLM ( 8 , 44 , 45 ). Another significant issue is using superselective catheterization for intraarterial BLM administration and balloon occlusion to prevent BLM washout during electroporation.…”
Section: Discussionmentioning
confidence: 99%